The influence of religious crusades on business activities and accounting / Mohamad Azmi Nias Ahmad - Ahmad, Mohamad Azmi Nias (Universiti Teknologi MARA Cawangan Pahang, 2002)
This article discusses the influence of Crusades on business activities and accounting. Crusades are series of wars by Western European Christians to recapture the Holy Land of Jerusalem from the Muslims. The Crusades result the need of accumulation of capital for both sides. Therefore, a systematic method was developed to document all the transactions in order to prevail in their campaign. Accounting was created in response to the development of trade and commerce.